2016
DOI: 10.1158/1535-7163.mct-15-0820
|View full text |Cite
|
Sign up to set email alerts
|

Nanofluidic Digital PCR and Extended Genotyping of RAS and BRAF for Improved Selection of Metastatic Colorectal Cancer Patients for Anti-EGFR Therapies

Abstract: The clinical significance of low-frequent RAS pathwaymutated alleles and the optimal sensitivity cutoff value in the prediction of response to anti-EGFR therapy in metastatic colorectal cancer (mCRC) patients remains controversial. We aimed to evaluate the added value of genotyping an extended RAS panel using a robust nanofluidic digital PCR (dPCR) approach. A panel of 34 hotspots, including RAS (KRAS and NRAS exons 2/3/4) and BRAF (V600E), was analyzed in tumor FFPE samples from 102 mCRC patients treated with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 34 publications
3
21
0
Order By: Relevance
“…[31][32][33] A subclone fraction as low as 1% for RAS pathway genes has been suggested to result in resistance to anti-EGFR therapy in CRC, with an inverse correlation between the mutated subclone fraction and the response. [34][35][36] Accordingly, the mutation detection threshold for the prediction of efficacy of anti-EGFR therapy should be prospectively investigated. The heterogeneity of mutated allele fractions among tumor lesions might result from subclonal expansion during metastatic progression, possibly affected by systemic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] A subclone fraction as low as 1% for RAS pathway genes has been suggested to result in resistance to anti-EGFR therapy in CRC, with an inverse correlation between the mutated subclone fraction and the response. [34][35][36] Accordingly, the mutation detection threshold for the prediction of efficacy of anti-EGFR therapy should be prospectively investigated. The heterogeneity of mutated allele fractions among tumor lesions might result from subclonal expansion during metastatic progression, possibly affected by systemic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, none of the studies reported above, including ours, have analyzed MAFs in light of microsatellite instability (MSI), which is associated with hypermutation rates and low copy number alterations (The Cancer Genome Atlas, 2012). Previous studies have found that the presence of a low fraction of KRAS-mutated cells within primary tumors may provide a reservoir for acquired resistance to EGFR antibodies (Azuara et al, 2016;Laurent-Puig et al, 2015). It is surprising that the measurement of MAFs in primary samples correlates with the effects of therapy in the metastatic setting, which suggests that in addition to concordance of mutation events in primary and metastatic samples, the relapsed lesions most likely retain a similar genomic structure, with the same distribution of MAFs.…”
Section: Discussionmentioning
confidence: 99%
“…In some scenarios, the MAFs of driver genes may have important clinical implications. Examples include the upfront resistance to anti-EGFR therapies in metastatic colorectal cancer (CRC) with KRAS MAFs as low as 1% (Azuara et al, 2016;Laurent-Puig et al, 2015), or the positive association between higher EGFR L858R MAFs in lung cancer specimens and longer duration of treatment benefit with gefitinib and erlotinib in the metastatic setting (Ono et al, 2014;Zhou et al, 2011). More recently, investigators have been tracking MAFs of driver genes to infer mutational timeline and depict dynamic clonal evolution in individual tumors exposed to targeted agents (McGranahan et al, 2015;Murtaza et al, 2015;Russo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Mutational analysis was conducted at the Institut Català d'Oncología (L'Hospitalet de Llobregat, Spain). DNA was extracted from formalinfixed paraffin-embedded tumour tissues (primary tumour or metastasis) and a 38-hotspot panel of KRAS (exons 2/3/4), NRAS (exons 2/3/4), BRAF (exon 15) and PIK3CA (exon 20) mutations was assessed using a conventional quantitative PCR (qPCR) machine (LightCycler V R 480; Roche Applied Science) and a nanofluidic dPCR platform (Digital Array TM and BioMark TM Real-Time PCR System; Fluidigm Europe) as described previously [11,12]. Mutations assessed in this study are described in supplementary Table S1, available at Annals of Oncology online.…”
Section: Mutational Analysismentioning
confidence: 99%
“…Nanofluidic dPCR improved the sensitivity of detecting KRAS-mutant alleles in clinical samples, reaching 0.05%-0.1%, and allows a better tumour classification with a commercially available platform [11]. Subsequent extended RAS and BRAF hotspot analyses suggested a threshold of 1% of mutated alleles to predict anti-EGFR therapy response, though the optimal cut-off for the clinical setting remains to be defined [12,13].…”
Section: Introductionmentioning
confidence: 99%